Comparative analysis of instantaneous wave-free ratio and quantitative real-time myocardial contrast echocardiography for the assessment of myocardial perfusion - Liang, Li; Zhu, Yongxiang; Li, Fangfang; Guo, Kai; Chang, Shang; Li, Qian; Zhang, Yaojun; Li, Dongye (Frontiers in Cardiovascular Medicine, 2022)
Background and hypothesis The field of coronary artery physiology is developing rapidly and changing the practice of interventional cardiology. A new functional evaluation technique using the instantaneous wave-free ratio (iFR) has become an alternative to fractional flow reserve. Future research studies need to determine whether physiological indicators play a role in evaluating myocardial perfusion in the catheter room. Materials and methods Thirty-eight patients scheduled for coronary angiography and iFR evaluation underwent a real-time myocardial contrast echocardiography (RT-MCE) examination at rest. The myocardial perfusion parameters (A, β, and A × β) on the myocardial perfusion curve were quantitatively analyzed using Q-Lab software. Coronary angiography and iFR assessment were completed within 1 week after the RT-MCE examination in all patients. Correlation analysis was used to identify iFR- and MCE-related indicators. The sensitivity and specificity of iFR in the quantitative detection of coronary microcirculation were obtained. Results The correlation coefficients between iFR and A, β, and A × β were 0.81, 0.66, and 0.82, respectively. The cut-off value for iFR was 0.85 for microvascular ischemia detection, while the sensitivity and specificity for the diagnosis of myocardial perfusion were 90.7 and 89.9%, respectively. The receiver operating characteristic (ROC) curve area for iFR was 0.946 in the segments related to myocardial blood flow. Conclusion The iFR is an effective tool for detecting myocardial microcirculation perfusion, with satisfactory diagnostic performance and a demonstrated role in physiological indices used for the perfusion assessment.